3D additive manufacture of oral and maxillofacial surgical models for preoperative planning - Zari Tehrani (The International Journal of Advanced Manufacturing Technology, 2014)
This paper investigates the errors generated during the fabrication stage for producing complex anatomical replicas derived from computed tomography coupled with the 3D additive manufacturing methods. Based on this research work, it is shown that patient-specific model based on computed tomography data can be converted into computer numerically controlled G-code. It is shown that 3D extrusion-based additive manufacturing technology is accurate to ±3 % equating to ±200 μm surface deviations due to plastic shrinkage and distortion formed during the process. Polylactic acid plastic extrusion through a 200-μm bore nozzle has resulted in a model being produced with an Ra roughness of 35.5 μm. An evaluation on the errors generated during the fabrication process has been used to accurately produce an adult female mandible. Internal nerve channels and complex external bone geometry has been produced within the model. It is shown that using this process results in bone complexity and accuracy required for producing low-cost surgical grades models which is in comparison with traditional selective laser sintering manufacturing techniques. The surface accuracies suggest that the reproduction of anatomically complex representative structures by 3D plastic extrusion additive manufacturing which can be used for pre-surgical planning.